Effect of automated drug distribution systems on medication error rates in a short‐stay geriatric unit. Issue 5 (11th June 2014) - Cousein, Etienne; Mareville, Julie; Lerooy, Alexandre; Caillau, Antoine; Labreuche, Julien; Dambre, Delphine; Odou, Pascal; Bonte, Jean‐Paul; Puisieux, François; Decaudin, Bertrand; Coupé, Patrick
Abstract Rationale, aims and objectives To assess the impact of an automated drug distribution system on medication errors (MEs). Methods Before‐after observational study in a 40‐bed short stay geriatric unit within a 1800 bed general hospital in Valenciennes, France. Researchers attended nurse medication administration rounds and compared administered to prescribed drugs, before and after the drug distribution system changed from a ward stock system (WSS) to a unit dose dispensing system (UDDS), integrating a unit dose dispensing robot and automated medication dispensing cabinet (AMDC). Results A total of 615 opportunities of errors (OEs) were observed among 148 patients treated during the WSS period, and 783 OEs were observed among 166 patients treated during the UDDS period. ME [medication administration error (MAE)] rates were calculated and compared between the two periods. Secondary measures included type of errors, seriousness of errors and risk reduction for the patients. The implementation of an automated drug dispensing system resulted in a 53% reduction in MAEs. All error types were reduced in the UDDS period compared with the WSS period (P < 0.001). Wrong dose and wrong drug errors were reduced by 79.1% (2.4% versus 0.5%, P = 0.005) and 93.7% (1.9% versus 0.01%, P = 0.009), respectively. Conclusion An automated UDDS combining a unit dose dispensing robot and AMDCs could reduce discrepancies between ordered and administered drugs, thus improving medication safety among the elderly.